2013
DOI: 10.1155/2013/428416
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis Design of a Split Rotor Bracket for a Bulb Turbine Generator

Abstract: The rotor bracket is a key component of the generator rotor with cracks in the rotor bracket leading to rubbing between the rotor and stator, which threatens safe operation of the unit. The rotor rim is so complicated that the equivalent radial stiffness of rim was determined by numerical simulation other than engineering experience. A comprehensive numerical method including finite element analyses and the contact method for multibody dynamics has been used to design the split rotor bracket. The com-putationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…They found that the stress caused by hydraulic force is one of the main reasons of the runner fatigue failures and cracks. In terms of the other essential components of pump turbines, Luo et al [32][33][34] focused on the stress of the rotor bracket of the generator and the piston rod of the blade. Improvements in design are made based on stress analyses.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the stress caused by hydraulic force is one of the main reasons of the runner fatigue failures and cracks. In terms of the other essential components of pump turbines, Luo et al [32][33][34] focused on the stress of the rotor bracket of the generator and the piston rod of the blade. Improvements in design are made based on stress analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In engineering applications, FEA allows optimization of weight, materials, costs and entire designs to be constructed, before the design is manufactured 15) . The FEA method has several advantages over other methods; at first, solid objects having complex geometry can be modeled with realistic assumptions of a material, by which a realistic model can be created using software.…”
Section: Introductionmentioning
confidence: 99%